Eksistensi Pengadilan Pajak Dalam Independensi Peradilan Penyelesaian Sengketa Pajak Ditinjau Dari Putusan Mahkamah Konstitusi Nomor 26/PUU-XII/2023 - Yapiter Marpi (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2023)
The existence of these judicial institutions becomes very important because it can be ascertained without the existence of judicial institutions that are given the authority to carry out law enforcement, then the law will not have much meaning in society. One of the judicial institutions tasked with carrying out law enforcement is the Tax Court Institute. So far, although the organization, administration and finance coaching is carried out by the Ministry of Finance, which incidentally is in charge of the DGT, does not reduce the freedom of the Tax Court and the independence of the judges in examining and deciding on existing tax disputes. Law enforcement in this context is the law in the field of taxation relating to the enforcement of the rights and obligations of the state and people in order to create the benefits, justice, and legal certainty for the parties. Then, through the decision of the Constitutional Court Number 26/PUU-XXI/2023 which mandates that the organizational, administrative, and finance foster of the Tax Court must be transferred to the Supreme Court, the provisions contained in the Tax Court Law regarding organizational development and technical guidance from the Supreme Court are also Administration and Finance by the Ministry of Finance does not describe the independence and independence of the judicial institution as mandated by Article 24 paragraph (1) of the 1945 Constitution of the Republic of Indonesia and the Law on Judiciary. As a result, by placing a tax court in the